Epigenetic Drug Therapy in the Treatment of Colorectal Cancer - Parizadeh, Seyed M.; Jafarzadeh-Esfehani, Reza; Ghandehari, Maryam; Seifi, Sima; Parizadeh, Seyed M. R.; Moetamani-Ahmadi, Mehrdad; Hassanian, Seyed Mahdi; Khazaei, Majid; Ghayour-Mobarhan, Majid; Ferns, Gordon A.; Avan, Amir (Current Pharmaceutical Design, 2018)
Colorectal Cancer (CRC) is one of the most common cancers with a high rate of morbidity and mortality worldwide. It has been demonstrated that epigenetic alterations which may cause changes in the expression of microRNA, DNA methylation and histone acetylation that results in inheritable modifications in gene expression in colorectal epithelial cells, plays a crucial role in the development of CRC. Recently, targeting epigenetic modification has emerged as a potentially important treatment approach in CRC. The US Food and Drug Association has approved the use of some epigenetic drugs that may be able to inhibit or reverse these alterations and also enhance sensitivity to chemotherapeutic agents and radiotherapy in CRC. In this review we have summarized the recent pre-clinical and clinical trial studies investigating the therapeutic value of using epigenetic drugs as novel therapeutic approach in CRC treatment.
Keywords: chemotherapeutic agents